'You'd be surprised how some people probably feel uncomfortable': the compliance–resistance continuum of planning integrated Australian History curricula. Issue 2 (15th March 2022) - Weuffen, Sara
ABSTRACT: The purpose of this article is to present a problematising and exploration of how teachers educated within settler-colonial systems are positioned to analyse critically and resist whitewashed curriculum when planning for school-based learning. Since the 2013 implementation of the Australian Curriculum: History, Aboriginal and Torres Strait Islander studies have been a mandatory, albeit subsidiary, focus area of study. While publications have explored the purpose of, the need for, and the possibilities offered up by cross-curriculum education, very little attention has been paid to how curriculum is enacted within schools. Through a poststructuralist lens, and a non-Indigenous researcher positioning, this article illuminates a discursive analysis of ways in which six history teachers in Victoria, Australia, perform their subject positioning along a continuum of compliance–resistance within the Australian education system.